Oregano Essential Oil Micro- and Nanoencapsulation With Bioactive Properties for Biotechnological and Biomedical Applications - Pontes-Quero, Gloria María; Esteban-Rubio, Susana; Pérez Cano, Juan; Aguilar, María Rosa; Vázquez-Lasa, Blanca (Frontiers in Bioengineering and Biotechnology, 2021)
Due to the preservative, antioxidant, antimicrobial and therapeutic properties of oregano essential oil, it has received an emerging interest for biotechnological and biomedical applications. However, stability and bioactivity can be compromised by its natural volatile and hydrophobic nature, and by external factors including light, heat or oxygen. Therefore, micro- and nanoencapsulation are being employed to guarantee oregano oil protection from outside aggressions and to maximize its potential. Oregano oil encapsulation is an interesting strategy used to increase its stability, enhance its bioactivity and decrease its volatility. At the same time, the versatility that micro- and nanocarriers offer, allow to prepare tailored systems that can provide a controlled and targeted release of the encapsulated principle, influence its bioactive activities or even provide additional properties. Most common materials used to prepare these carriers are based on lipids and cyclodextrins, due to its hydrophobic nature, polymers due to its versatility in composition and hybrid lipid-polymer systems. In this context, recently developed micro- and nanocarriers encapsulating oregano oil with applications in the biotechnological and biomedical fields will be discussed.